Antidiabetic activity test result of fractionation of Bengkal Leaves (Nauclea orientalis L.) on male white mice - Brata, Andy; Azizah, Lailan (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2024)
Background: Bengkal leaves (Nauclea orientalis L.) is a plant that contains flavonoids as active substances to reduce blood glucose levels (antidiabetic). The use of a decoction of bengkal leaves (Nauclea orientalis L.) which has been used in the community as an antidiabetic has not yet been determined for its pharmacological activity. This research was conducted to test the activity of Bengkal leaf fractions (Nauclea orientalis L.) which were used as antidiabetic in male white mice that had been previously induced with alloxan. Method: This research is a quasi-experimental research using the static-group comparison design. The test animals used were 35 male white mice which were divided into 7 groups, namely negative control group (tragacanth), positive control group (alloxan), comparison group (glibenclamide), ethanol extract group, n-hexane fraction, ethyl acetate and Bengkal leaf water at a dose of 150mg/kgBW. After that, testing was carried out by checking the blood glucose levels of the mice starting from days 1, 3 to 7. Followed by a one-way ANOVA statistical test to obtain significant results on which day was the most effective. Then use the post hoc Duncan test to find out the best fraction that has an effect close to glibenclamide 5 mg. So it will be known whether the Bengkal leaf fraction (Nauclea orientalis L.) is effective as an antidiabetic. In the end, we will find out whether the Bengkal leaf fraction can be used as an antidiabetic drug. Results: There is antidiabetic activity after administration of various fractions of Bengkal leaves to male white mice induced by alloxan. Conclusion: Administration of ethyl acetate fraction of Bengkal leaves has antidiabetic activity in male white mice almost equivalent to glibenclamide. Bengkal leaf fraction has potential as an antidiabetic drug.